Dietary linseed oil affects the polyunsaturated fatty acid and transcriptome profiles in the livers and breast muscles of ducks - Wang, Laidi; Dong, Bingqiang; Yang, Ting; Zhang, Ao; Hu, Xiaodan; Wang, Zhixiu; Chang, Guobin; Chen, Guohong (Frontiers in Nutrition, 2022)
Linseed oil, an important source of dietary α-linolenic acid, is used to provide meat enriched in n-3 PUFA. We investigated the effects of dietary linseed oil (0%, 0.5%, 1% and 2%) on growth performance, meat quality, tissue fatty acid and transcriptome profiles in ducks. The result showed that dietary linseed oil had no effect on growth performance. Increasing dietary linseed oil enrichment raised n-3 PUFA and linoleic acid (LA) levels in both the liver and breast muscle, but decreased dihomo-gamma-linolenic acid (DGLA) and arachidonic acid (ARA) levels in the liver. The liver n-3 PUFA content was negatively correlated with duck body weight. Transcriptome analysis showed that dietary linseed oil caused hepatic changes in genes (SCD, FADS1, FADS2, and ACOT6) related to the biosynthesis of unsaturated fatty acids. Besides, dietary linseed oil also affected the expression of genes related to PUFAs and downstream metabolites (such as linoleic acid, steroid hormone, progesterone, etc.) metabolic pathways in both liver and breast muscle. Key genes involved in PUFA synthesis and transport pathways were examined by RT-qPCR, and the results verified that hepatic expression levels of FADS1 and FADS2 decreased, and those of FABP4 and FABP5 increased when 2% linseed oil was added. CD36 expression level increased in breast muscle when 2% linseed oil was added. Thus, 2% dietary linseed oil supplementation produces n-3 PUFA-enriched duck products by regulating the PUFA metabolic pathways, which could be advantageous for health-conscious consumers.